Polymer-dispersed liquid crystal film
The PDLC film addresses the limitations of conventional PDLC films by incorporating specific liquid crystal components and dichroic dyes, allowing it to switch between transparent and colored states, thereby enhancing design flexibility.
Patent Information
- Application Number
- JP2023169972
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Conventional polymer-dispersed liquid crystal (PDLC) films can only switch between a cloudy and transparent state, limiting their design flexibility for applications requiring different appearances.
A PDLC film with a first region containing non-polymerizable liquid crystal components, liquid crystal polymers, and dichroic dyes, and a second region with non-polymerizable and polymerizable liquid crystal components, and dichroic dyes, allowing for switching between transparent and colored states in a desired pattern.
The film effectively suppresses changes in haze and coloring in the region with liquid crystal polymers while allowing changes in other regions, enabling the creation of complex appearance patterns.
Smart Images

Figure 2025059711000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer dispersed liquid crystal film. [Background technology]
[0002] 2. Description of the Related Art In recent years, light control films that exhibit different appearances depending on the applied voltage state have been applied to various applications such as advertisements, displays such as guide boards, smart windows, and the like.
[0003] A PDLC film having a polymer dispersed liquid crystal (hereinafter sometimes referred to as "PDLC") layer between a pair of transparent electrode layers is a type of light control film, and can switch between a light scattering state (scattering state) and a light transmitting state (non-scattering state or transparent state) by switching between a voltage application state and a voltage non-application state. Specifically, the PDLC layer contains a polymer matrix and droplets of a liquid crystal component (liquid crystal droplets) dispersed in the polymer matrix, and the liquid crystal droplets become scattering particles due to the refractive index difference between the liquid crystal component in the liquid crystal droplets and the polymer matrix, and can cause light scattering (for example, Patent Document 1).
[0004] The above-mentioned PDLC film generally has a cloudy appearance in the scattering state, and can therefore exhibit two appearances: cloudy (scattering state) and transparent (non-scattering state). However, taking design into consideration, there is a demand for light-control films that can exhibit other appearances. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2021-60521 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made to solve the above-mentioned problems in the conventional art, and its main object is to provide a polymer dispersed liquid crystal film that can have high designability, specifically, a polymer dispersed liquid crystal film that can be switched between a transparent state and a colored state in a desired pattern. [Means for solving the problem]
[0007] [1] According to one aspect of the present invention, there is provided a polymer dispersed liquid crystal film comprising, in this order, a first transparent conductive film, a polymer dispersed liquid crystal layer comprising a polymer matrix and liquid crystal droplets dispersed in the polymer matrix, and a second transparent conductive film, wherein the polymer dispersed liquid crystal layer has a first region in which the liquid crystal droplets comprise a non-polymerizable liquid crystal component, a liquid crystal polymer, and a dichroic dye, and a second region in which the liquid crystal droplets comprise a non-polymerizable liquid crystal component, a polymerizable liquid crystal component, and a dichroic dye. [2] In the polymer dispersed liquid crystal film described in [1] above, a change in transmittance at the absorption peak wavelength of the dichroic dye in the first region due to application of a voltage may be smaller than a change in the transmittance in the second region. [3] In the polymer dispersed liquid crystal film according to the above [1] or [2], the liquid crystal droplets may have an average particle size of 1 μm or less. [4] In the polymer dispersed liquid crystal film according to any one of [1] to [3] above, the content of the liquid crystal polymer in the first region may be 1 part by weight to 30 parts by weight per 100 parts by weight of the non-polymerizable liquid crystal component. [5] In the polymer dispersed liquid crystal film according to any one of [1] to [4] above, the content of the dichroic dye in the first region may be 0.1 to 10 parts by weight relative to 100 parts by weight of the non-polymerizable liquid crystal component. [6] In the polymer dispersed liquid crystal film according to any one of the above [1] to [5], the difference between the haze of the first region and the haze of the second region may be increased by application of a voltage. [7] In the polymer dispersed liquid crystal film according to any one of the above [1] to [5], the difference between the haze of the first region and the haze of the second region may be reduced by application of a voltage. [8] The polymer dispersed liquid crystal film according to any one of [1] to [7] above may further include a reflective layer on the side of the first transparent conductive film or the second transparent conductive film opposite to the side on which the polymer dispersed liquid crystal layer is disposed. Effect of the Invention
[0008] According to an embodiment of the present invention, the orientation of the liquid crystal component is regulated in the liquid crystal droplets in which the liquid crystal polymer exists, and the liquid crystal droplets contain a dichroic dye, so that changes in haze and coloring caused by changes in the voltage application state are suppressed. Therefore, by changing the voltage application state in a state in which the liquid crystal polymer exists in the liquid crystal droplets in a desired region, it is possible to change the haze and coloring state in the other regions while suppressing changes in the haze and coloring state in that region. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1A is a schematic plan view of an example of a PDLC film according to an embodiment of the present invention, FIG. 1B is a schematic cross-sectional view illustrating the state of the PDLC film shown in FIG. 1A when no voltage is applied, and FIG. 1C is a schematic cross-sectional view illustrating the state of the PDLC film shown in FIG. 1A when a voltage is applied. [Diagram 2] FIG. 1A is a schematic plan view of another example of a PDLC film according to an embodiment of the present invention, FIG. 1B is a schematic cross-sectional view illustrating the state of the PDLC film shown in FIG. 1A when no voltage is applied, and FIG. 1C is a schematic cross-sectional view illustrating the state of the PDLC film shown in FIG. 1A when a voltage is applied. [Diagram 3] 1A and 1B are schematic cross-sectional views illustrating the state of another example of a PDLC film according to an embodiment of the present invention when no voltage is applied and when a voltage is applied, respectively. [Figure 4] FIG. 2 is a schematic diagram illustrating an example of a method for producing a PDLC film of the present invention. [Diagram 5] FIG. 2 is a schematic diagram illustrating an example of a method for producing a PDLC film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, preferred embodiments of the present invention will be described, but the present invention is not limited to these embodiments. In addition, each embodiment can be appropriately combined. In this specification, "~" representing a numerical range includes the upper and lower limit numerical values. In order to make the explanation clearer, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the embodiment, but it is merely an example and does not limit the interpretation of the present invention.
[0011] A. Polymer-dispersed liquid crystal film 1(a) is a schematic plan view of an example of a polymer dispersed liquid crystal (PDLC) film according to one embodiment of the present invention, (b) is a schematic cross-sectional view illustrating the state of the PDLC film shown in (a) when no voltage is applied, and (c) is a schematic cross-sectional view illustrating the state of the PDLC film shown in (a) when a voltage is applied. The PDLC film 100a includes, in this order, a first transparent conductive film 10, a PDLC layer 20 including a polymer matrix 22 and liquid crystal droplets 24 dispersed in the polymer matrix 22, and a second transparent conductive film 30. The PDLC layer 20 has a first region A in which the liquid crystal droplets 24 contain a non-polymerizable liquid crystal component 24a, a liquid crystal polymer 24c, and a dichroic dye 24d, and a second region B in which the liquid crystal droplets 24 contain a non-polymerizable liquid crystal component 24a, a polymerizable liquid crystal component 24b, and a dichroic dye 24d.
[0012] As shown in FIG. 1(b), in the PDLC film 100a when no voltage is applied, the non-polymerizable liquid crystal component 24a, the liquid crystal polymer 24c, and the dichroic dye 24d in the liquid crystal droplet 24 in the first region A are all in a non-oriented state. In addition, the non-polymerizable liquid crystal component 24a, the polymerizable liquid crystal component 24b, and the dichroic dye 24d in the liquid crystal droplet 24 in the second region B are all in a non-oriented state. Therefore, in both the first region A and the second region B, scattering of transmitted light due to the difference in refractive index between the polymer matrix and the liquid crystal component and / or the liquid crystal polymer and absorption by the dichroic dye occur. Therefore, both the first region A and the second region B may be in a colored scattering state, and as a result, the entire main surface of the PDLC film 100a when no voltage is applied may be in a colored scattering state. In this specification, a compound being "in a non-oriented state" means that the compound is not aligned with a certain regularity.
[0013] On the other hand, as shown in FIG. 1(c), in the PDLC film 100a when a voltage is applied, the non-polymerizable liquid crystal component 24a, the polymerizable liquid crystal component 24b, and the dichroic dye 24d in the liquid crystal droplet 24 in the second region B are all oriented in a predetermined direction (thickness direction in the illustrated example). Therefore, in the second region B, scattering and absorption of transmitted light are suppressed, and as a result, the haze is low (transparent) and the coloring is light (colorless). On the other hand, in the first region A, the orientation of the non-polymerizable liquid crystal component 24a and the dichroic dye 24d is regulated by the presence of the liquid crystal polymer 24c in a non-oriented state, and the non-oriented state is maintained. Therefore, in the first region A, scattering and absorption of transmitted light occurs in the same way as when no voltage is applied. As a result, in the PDLC film 100a when a voltage is applied, the first region A may be in a colored scattering state, and the second region B may be in a colorless and transparent state. However, the colorless and transparent state means that the haze is lower and the color is lighter than the colored scattering state, and it does not have to be completely colorless and transparent.
[0014] In the PDLC film 100a, the change in haze in the first region A due to the application of a voltage is smaller than the change in the second region B, and the difference between the haze in the first region A and the haze in the second region B increases due to the application of a voltage. A The change in the transmittance T A The change in the transmittance T A and the transmittance T of the second region B A The difference between increases with application of voltage.
[0015] The haze of the region of the PDLC film corresponding to the first region when no voltage is applied (hereinafter, may be simply referred to as "haze of the first region") is, for example, 50% to 100%, preferably 70% to 100%. The haze of the first region when a voltage is applied is, for example, 40% to 100%, preferably 60% to 100%. The change in haze of the first region due to application of a voltage (|haze when no voltage is applied - haze when voltage is applied|) is, for example, 0% to 40%, preferably 0% to 30%.
[0016] The haze of the region of the PDLC film corresponding to the second region when no voltage is applied (hereinafter, may be simply referred to as "the haze of the second region") is, for example, 50% to 100%, preferably 70% to 100%. The haze of the second region when a voltage is applied is, for example, 1% to 20%, preferably 1% to 10%. The change in the haze of the second region due to the application of a voltage (|haze when no voltage is applied - haze when voltage is applied|) is, for example, 30% to 99%, preferably 60% to 99%.
[0017] The difference between the amount of change in haze in the first region due to application of a voltage and the amount of change in haze in the second region due to application of a voltage is, for example, 10% to 99%, and preferably 30% to 99%.
[0018] The transmittance T in the region corresponding to the first region and the region corresponding to the second region of the PDLC film when no voltage is applied Acan vary depending on the type and blending ratio of the dichroic dye, and can be appropriately set depending on the purpose.
[0019] The transmittance T of the region of the PDLC film corresponding to the first region when no voltage is applied A (Hereinafter, simply "transmittance T of the first region A The transmittance T of the first region when a voltage is applied is, for example, 40% to 90%, and preferably 40% to 70%. A The transmittance T of the first region due to the application of a voltage is, for example, 40% to 95%, and preferably 40% to 70%. A The change in transmittance when no voltage is applied (|T A -Transmittance when voltage is applied T A |) is, for example, 0% to 10%, or, for example, 0% to 5%.
[0020] The transmittance T of the region of the PDLC film corresponding to the second region when no voltage is applied A (Hereinafter, simply "transmittance T of the second region A The transmittance T of the second region when a voltage is applied is, for example, 40% to 90%, and preferably 40% to 70%. A The transmittance T of the second region by applying a voltage is, for example, 45% to 95%, and preferably 60% to 95%. A The change in transmittance when no voltage is applied (|T A -Transmittance when voltage is applied T A |) is, for example, 5% to 30%, or, for example, 5% to 20%.
[0021] Transmittance T of the first region by applying voltage A and the transmittance T of the second region due to the application of voltage A The difference from the amount of change is, for example, 5% to 25%, or, for example, 5% to 20%.
[0022] The voltage applied to the PDLC film during voltage application is a voltage capable of operating the PDLC film (operating voltage), and may be, for example, 5 V to 200 V, and preferably 10 V to 100 V. In this specification, "when a voltage is applied" refers to a state in which an operating voltage is applied to the PDLC film, and may be, for example, a state in which a voltage of 30 V is applied.
[0023] The thickness of the PDLC film is, for example, 30 μm to 250 μm, and preferably 50 μm to 150 μm.
[0024] A-1. First transparent conductive film The first transparent conductive film 10 typically includes a first transparent substrate 12 and a first transparent electrode layer 14 provided on one side thereof. The first transparent conductive film 10 may have a hard coat layer on one or both sides of the first transparent substrate 12, and may also have a refractive index adjusting layer between the first transparent substrate 12 and the first transparent electrode layer 14, as necessary.
[0025] The surface resistance value of the first transparent conductive film is preferably 1 Ω / □ to 1000 Ω / □, more preferably 5 Ω / □ to 300 Ω / □, and further preferably 10 Ω / □ to 200 Ω / □.
[0026] The haze of the first transparent conductive film is preferably 20% or less, more preferably 10% or less, and further preferably 0.1% to 10%.
[0027] The total light transmittance of the first transparent conductive film is preferably 30% or more, more preferably 60% or more, and further preferably 80% or more.
[0028] The first transparent substrate can be formed using any appropriate material. Specifically, for example, a polymer substrate such as a film or a plastic substrate is preferably used. This is because it has excellent smoothness and wettability with respect to the transparent electrode layer forming composition, and the productivity can be significantly improved by continuous production using a roll.
[0029] Typically, the first transparent substrate is a polymer film mainly composed of a thermoplastic resin. Examples of the thermoplastic resin include polyester resins; cycloolefin resins such as polynorbornene; acrylic resins; polycarbonate resins; and cellulose resins. Among these, polyester resins, cycloolefin resins, and acrylic resins are preferred. These resins are excellent in transparency, mechanical strength, thermal stability, and moisture shielding properties. The above thermoplastic resins may be used alone or in combination of two or more.
[0030] The thickness of the first transparent substrate is preferably 200 μm or less, more preferably 3 μm to 100 μm, and further preferably 5 μm to 70 μm. By setting the thickness of the first transparent substrate to 200 μm or less, the function of the PDLC layer can be fully exhibited.
[0031] The total light transmittance of the first transparent substrate is preferably 30% or more, more preferably 60% or more, and further preferably 80% or more.
[0032] The first transparent electrode layer is made of, for example, indium tin oxide (ITO), zinc oxide (ZnO), tin oxide (SnO 2 The first transparent electrode layer may be formed using a metal oxide such as ZnO. In this case, the metal oxide may be an amorphous metal oxide or a crystallized metal oxide. The first transparent electrode layer may also be formed of a metal nanowire such as a silver nanowire (AgNW), a carbon nanotube (CNT), an organic conductive film, a metal layer, or a laminate thereof. Preferably, a transparent electrode layer containing ITO is formed. The transparent electrode layer containing ITO has excellent transparency. The first transparent electrode layer may be patterned into a desired shape depending on the purpose.
[0033] The total light transmittance of the first transparent electrode layer is preferably 85% or more, more preferably 87% or more, and even more preferably 90% or more. By using a transparent electrode layer having a total light transmittance in such a range, a PDLC film having a high total light transmittance in a transparent state can be obtained. The higher the total light transmittance, the more preferable it is, and the upper limit is, for example, 99%.
[0034] The thickness of the first transparent electrode layer is, for example, 10 nm or more, and preferably 15 nm or more.The thickness of the first transparent electrode layer is, for example, 50 nm or less, preferably 35 nm or less, and more preferably 30 nm or less.
[0035] The first transparent electrode layer is provided on one surface of the first transparent substrate by, for example, sputtering. After forming the metal oxide layer by sputtering, it can be crystallized by annealing. The annealing is performed by, for example, heat treatment at 120°C to 300°C for 10 minutes to 120 minutes.
[0036] The refractive index adjusting layer and the hard coat layer may have a structure well known in the art, and therefore detailed description of the structure will be omitted.
[0037] A-2.PDLC layer The PDLC layer 20 includes a polymer matrix 22 and droplets of a liquid crystal component (liquid crystal droplets) 24 dispersed in the polymer matrix 22. As shown in Fig. 1, the PDLC layer 20 has a first region A and a second region B. The liquid crystal droplets 24 in the first region A include a non-polymerizable liquid crystal component 24a, a liquid crystal polymer 24c, and a dichroic dye 24d, and the liquid crystal droplets 24 in the second region B include a non-polymerizable liquid crystal component 24a, a polymerizable liquid crystal component 24b, and a dichroic dye 24d. The first region A and the second region B may be formed in any appropriate pattern depending on the design desired for the PDLC film.
[0038] The polymer matrix may be composed of any appropriate resin. The resin for forming the polymer matrix may be appropriately selected depending on the light transmittance, the refractive index of the liquid crystal component, the adhesion to the transparent conductive film, and the like. For example, water-soluble or water-dispersible resins such as urethane-based resins, polyvinyl alcohol-based resins, polyethylene-based resins, polypropylene-based resins, and acrylic-based resins may be preferably used. The resin for forming the polymer matrix may be used alone or in combination.
[0039] As the non-polymerizable liquid crystal component, any non-polymerizable liquid crystal compound can be used alone or in combination of two or more depending on the birefringence, compatibility with the polymerizable liquid crystal component, etc. In the following description, the characteristics of the liquid crystal component (birefringence, dielectric constant, etc.) refer to the characteristics of the liquid crystal component as a whole, which may contain multiple liquid crystal compounds.
[0040] The birefringence (Δn=refractive index of the liquid crystal component in the major axis direction, no is the refractive index of the liquid crystal component in the minor axis direction) of the non-polymerizable liquid crystal component at a wavelength of 589 nm is preferably 0.05 to 0.50, more preferably 0.10 to 0.45.
[0041] In the illustrated example, a non-polymerizable liquid crystal component having positive dielectric anisotropy is used, but the dielectric anisotropy of the non-polymerizable liquid crystal component may be either positive or negative.
[0042] The non-polymerizable liquid crystal component may be, for example, a nematic, smectic, or cholesteric liquid crystal component. It is preferable to use a nematic liquid crystal component because it can achieve excellent transparency in the transparent state.
[0043] Examples of nematic liquid crystal compounds include biphenyl-based compounds, phenylbenzoate-based compounds, cyclohexylbenzene-based compounds, azoxybenzene-based compounds, azobenzene-based compounds, azomethine-based compounds, terphenyl-based compounds, biphenylbenzoate-based compounds, cyclohexylbiphenyl-based compounds, phenylpyridine-based compounds, cyclohexylpyrimidine-based compounds, cholesterol-based compounds, fluorine-based compounds, etc. These low molecular weight liquid crystal compounds may be used alone or in combination.
[0044] As the polymerizable liquid crystal component, any polymerizable liquid crystal compound can be used alone or in combination of two or more depending on the birefringence, compatibility with the non-polymerizable liquid crystal component, etc. The polymerizable liquid crystal compound may be a crosslinked type having two or more functionalities. As the polymerizable liquid crystal compound, for example, polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445, etc. can be used. As a specific example of such a polymerizable mesogen compound, for example, BASF's product name LC242 can be mentioned. As the polymerizable liquid crystal compound, for example, a nematic type liquid crystal monomer is preferable.
[0045] The birefringence (Δn=refractive index of the liquid crystal component in the major axis direction, no is the refractive index of the liquid crystal component in the minor axis direction) of the polymerizable liquid crystal component at a wavelength of 589 nm is preferably 0.05 to 0.50, more preferably 0.10 to 0.45.
[0046] A liquid crystal polymer is typically a polymerization product of the above-mentioned polymerizable liquid crystal component. A polymer is formed by polymerization of the polymerizable liquid crystal component, and a network structure can be formed by crosslinking, but these are non-liquid crystals. Therefore, in liquid crystal polymers, for example, transition to a liquid crystal phase, glass phase, or crystal phase due to temperature change, which is specific to liquid crystal compounds, does not occur.
[0047] The liquid crystal polymer is typically present in a non-oriented state in the liquid crystal droplets. Since the liquid crystal polymer in the liquid crystal droplets is in a non-oriented state, the first region can maintain a high haze (for example, 40% to 100%, preferably 60% to 100%) even when a voltage is applied.
[0048] As the dichroic dye, any appropriate dichroic dye compatible with the non-polymerizable liquid crystal component and the polymerizable liquid crystal component (these may be collectively referred to as "liquid crystal components") can be used. The dichroic dye may have a positive Δε or a negative Δε. The dichroic dye itself may exhibit liquid crystallinity. Only one dichroic dye may be used, or two or more dichroic dyes may be used in combination.
[0049] Specific examples of the dichroic dye include azo dyes, anthraquinone dyes, naphthoquinone dyes, perylene dyes, quinophthalone dyes, tetrazine dyes, and benzothiadiazole dyes. Among them, from the viewpoints of absorption coefficient, solubility in liquid crystal components, light resistance, and the like, it is preferable that the dichroic dye contains anthraquinone dyes or azo dyes. For example, azo dyes, anthraquinone dyes, or mixtures thereof described in "Liquid Crystal Device Handbook" edited by the 142nd Committee of the Japan Society for the Promotion of Science, Japan Industrial Newspaper Co., Ltd. (1989), pages 192 to 196 and 724 to 730 can be used. In addition, various dichroic dyes are commercially available, and these can be used as appropriate.
[0050] The content of the polymer matrix in the PDLC layer is, for example, 30% to 70% by weight, preferably 35% to 65% by weight, and more preferably 40% to 60% by weight in both the first and second regions. If the content of the polymer matrix is within the above range, it is possible to obtain effects such as a good light control function at a moderate operating voltage, good mechanical strength, and prevention of liquid crystal leakage from the edges.
[0051] The ratio of the content of the polymer matrix in the first region to the total content of the non-polymerizable liquid crystal component, the liquid crystal polymer, and the dichroic dye (the former:the latter (by weight)) is 30:70 to 70:30, preferably 35:65 to 65:35, and more preferably 40:60 to 60:40. The content of the liquid crystal polymer in the first region can be, for example, 1 to 30 parts by weight, and preferably 5 to 20 parts by weight, relative to 100 parts by weight of the non-polymerizable liquid crystal component. The content of the dichroic dye in the first region can be, for example, 0.1 to 10 parts by weight, and preferably 0.5 to 7 parts by weight, relative to 100 parts by weight of the non-polymerizable liquid crystal component. The total content of the polymer matrix, non-polymerizable liquid crystal component, liquid crystal polymer, and dichroic dye in the first region can typically be 80% by weight to 100% by weight, for example 90% by weight to 99.9% by weight, and preferably 95% by weight to 99.9% by weight.
[0052] The ratio of the content of the polymer matrix in the second region to the total content of the non-polymerizable liquid crystal component, the polymerizable liquid crystal component, and the dichroic dye (the former:the latter (by weight)) is 30:70 to 70:30, preferably 35:65 to 65:35, and more preferably 40:60 to 60:40. The content of the polymerizable liquid crystal component in the second region can be, for example, 1 to 30 parts by weight, and preferably 5 to 20 parts by weight, relative to 100 parts by weight of the non-polymerizable liquid crystal component. The content of the dichroic dye in the second region can be, for example, 0.1 to 10 parts by weight, and preferably 0.5 to 7 parts by weight, relative to 100 parts by weight of the non-polymerizable liquid crystal component. The total content of the polymer matrix, non-polymerizable liquid crystal component, polymerizable liquid crystal component, and dichroic dye in the second region can typically be 80% by weight to 100% by weight, for example 90% by weight to 99.9% by weight, and preferably 95% by weight to 99.9% by weight.
[0053] Unreacted polymerizable liquid crystal components may remain in the liquid crystal droplets in the first region. The content of unreacted polymerizable liquid crystal components in the first region is, for example, 3% by weight or less, preferably 1% by weight or less. It is preferable that the liquid crystal droplets in the second region are substantially free of liquid crystal polymer. The content of liquid crystal polymer in the second region is, for example, 3% by weight or less, preferably 1% by weight or less.
[0054] The PDLC layer may further include any suitable additive, if necessary. As described in detail in Section B, a PDLC layer having a first region and a second region may be formed by polymerizing a polymerizable liquid crystal component in a predetermined region of a PDLC layer containing liquid crystal droplets containing a non-polymerizable liquid crystal component, a polymerizable liquid crystal component, and a dichroic dye to form a liquid crystal polymer, in which case the predetermined region becomes the first region and the other region becomes the second region. Thus, the PDLC layer (more specifically, the liquid crystal droplets) may further include a polymerization initiator. Other additives include a surfactant, a leveling agent, a crosslinking agent, a dispersion stabilizer, and the like.
[0055] As the polymerization initiator, any appropriate photopolymerization initiator can be used depending on the purpose, desired properties, and the like. Specific examples of photopolymerization initiators include 2,2-dimethoxy-2-phenylacetophenone, acetophenone, benzophenone, xanthone, 3-methylacetophenone, 4-chlorobenzophenone, 4,4'-dimethoxybenzophenone, benzoin propyl ether, benzyl dimethyl ketal, N,N,N',N'-tetramethyl-4,4'-diaminobenzophenone, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis-(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-dipentoxyphenylphosphine oxide, bis(2,6-dimethoxy-benzoyl)-(2,4,4-trimethyl-pentyl)-phosphine oxide, and thioxanthone compounds. The photopolymerization initiators may be used alone or in combination of two or more. The content of the photopolymerization initiator is, for example, 0.1 to 10 parts by weight, and preferably 0.5 to 5 parts by weight, relative to 100 parts by weight of the polymerizable liquid crystal component.
[0056] Examples of the dispersant include anionic surfactants, cationic surfactants, amphoteric surfactants, nonionic surfactants, etc. The content of the dispersant in the PDLC layer is, for example, 1% by weight to 15% by weight, and preferably 2% by weight to 10% by weight.
[0057] Examples of the leveling agent include an acrylic leveling agent, a fluorine-based leveling agent, a silicone-based leveling agent, etc. The content of the leveling agent in the PDLC layer is, for example, 0.1% by weight to 10% by weight, and preferably 0.5% by weight to 5% by weight.
[0058] Examples of the crosslinking agent include aziridine-based crosslinking agents and isocyanate-based crosslinking agents. The content ratio of the crosslinking agent in the PDLC layer is, for example, 0.5% by weight to 20% by weight, preferably 1% by weight to 10% by weight.
[0059] The average particle diameter of the liquid crystal droplets is typically 1 μm or less, for example, 0.5 μm or less. Since a PDLC layer containing liquid crystal droplets with a small particle diameter has low scattering properties, a PDLC film with high transparency in the transparent state (for example, a PDLC film with high transparency in the second region B when a voltage is applied) can be obtained by setting the average particle diameter of the liquid crystal droplets to 1 μm or less. From the viewpoint of obtaining higher transparency, the average particle diameter of the liquid crystal droplets is preferably equal to or less than the wavelength of visible light. Specifically, the average particle diameter of the liquid crystal droplets is preferably less than 0.38 μm, more preferably less than 0.3 μm, still more preferably less than 0.2 μm, even more preferably 0.18 μm or less, even more preferably 0.15 μm or less, and even more preferably 0.12 μm or less. The lower limit of the average particle diameter of the liquid crystal droplets can be, for example, 0.01 μm or more or 0.05 μm or more. The average particle diameter of the liquid crystal droplets is the volume average particle diameter of the liquid crystal droplets when viewed from a direction perpendicular to the main surface of the PDLC film, and can be obtained, for example, by the method described below. <Method for Measuring the Average Particle Diameter of Liquid Crystal Droplets in the PDLC Layer> Slice the PDLC film horizontally in a cooling environment, and smooth the exposed horizontal cross-section of the PDLC layer with a microtome. Next, observe the horizontal cross-section of the PDLC layer with a scanning electron microscope (SEM) to obtain a cross-sectional SEM image. In the cross-sectional SEM image, calculate the equivalent circle diameter (Heywood diameter) from the cross-sectional areas of all the liquid crystal droplets in a predetermined region (for example, a region of 30 μm × 20 μm), and calculate the volume average particle diameter (median diameter) by taking a statistic weighted by the volume estimated for each equivalent diameter.
[0060] The thickness of the PDLC layer is typically 2 μm to 40 μm, preferably 3 μm to 35 μm, and more preferably 4 μm to 30 μm.
[0061] A-3. Second transparent conductive film The second transparent conductive film 30 typically has a second transparent substrate 32 and a second transparent electrode layer 34 provided on one side thereof. The second transparent conductive film 30 may have a hard coat layer on one or both sides of the second transparent substrate 32, and may have a refractive index adjusting layer between the second transparent substrate 32 and the second transparent electrode layer 34, as necessary.
[0062] The surface resistance value of the second transparent conductive film is preferably 1 Ω / □ to 1000 Ω / □, more preferably 5 Ω / □ to 300 Ω / □, and further preferably 10 Ω / □ to 200 Ω / □.
[0063] The haze value of the second transparent conductive film is preferably 20% or less, more preferably 10% or less, and further preferably 0.1% to 10%.
[0064] The total light transmittance of the second transparent conductive film is preferably 30% or more, more preferably 60% or more, and further preferably 80% or more.
[0065] The second transparent substrate and the second transparent electrode layer can be described in the same manner as the first transparent substrate and the first transparent electrode layer, respectively. The second transparent conductive film may have the same structure as the first transparent conductive film, or may have a different structure.
[0066] A-4. Variation 1 2(a) is a schematic plan view of an example of a PDLC film according to another embodiment of the present invention, (b) is a schematic cross-sectional view illustrating the state of the PDLC film shown in (a) when no voltage is applied, and (c) is a schematic cross-sectional view illustrating the state of the PDLC film shown in (a) when a voltage is applied. The PDLC film 100b includes, in this order, a first transparent conductive film 10, a PDLC layer 20 including a polymer matrix 22 and liquid crystal droplets 24 dispersed in the polymer matrix 22, and a second transparent conductive film 30. The PDLC layer 20 has a first region A in which the liquid crystal droplets 24 contain a non-polymerizable liquid crystal component 24a, a liquid crystal polymer 24c, and a dichroic dye 24d, and a second region B in which the liquid crystal droplets 24 contain a non-polymerizable liquid crystal component 24a, a polymerizable liquid crystal component 24b, and a dichroic dye 24d.
[0067] As shown in FIG. 2(b), in the PDLC film 100b when no voltage is applied, the liquid crystal polymer 24c in the liquid crystal droplet 24 in the first region A is oriented in a predetermined direction (thickness direction in the illustrated example), and the non-polymerizable liquid crystal component 24a and the dichroic dye 24d are also oriented in the above-mentioned predetermined direction due to the orientation restriction by the liquid crystal polymer 24c. Therefore, in the first region A, scattering and absorption of transmitted light are suppressed, the haze is low, and the coloring is light. On the other hand, the non-polymerizable liquid crystal component 24a, the polymerizable liquid crystal component 24b, and the dichroic dye 24d in the liquid crystal droplet 24 in the second region B are all in a non-oriented state. Therefore, in the second region B, scattering of transmitted light due to the refractive index difference between the polymer matrix and the liquid crystal component and absorption by the dichroic dye occur. As a result, in the PDLC film 100b when no voltage is applied, the first region A may be in a colorless and transparent state, and the second region B may be in a colored and scattered state.
[0068] On the other hand, as shown in FIG. 2(c), in the PDLC film 100b when a voltage is applied, the non-polymerizable liquid crystal component 24a, the liquid crystal polymer 24c, and the dichroic dye 24d in the liquid crystal droplet 24 in the first region A are all oriented in a predetermined direction (thickness direction in the illustrated example). In addition, the non-polymerizable liquid crystal component 24a, the polymerizable liquid crystal component 24b, and the dichroic dye 24d in the liquid crystal droplet 24 in the second region B are all oriented in a predetermined direction (thickness direction in the illustrated example). Therefore, in both the first region A and the second region B, scattering and absorption of transmitted light are suppressed, resulting in low haze and light coloring. As a result, the entire main surface of the PDLC film 100b when a voltage is applied can be in a colorless and transparent state.
[0069] In the PDLC film 100b, the change in haze in the first region A due to the application of a voltage is smaller than the change in the second region B, and the difference between the haze in the first region A and the haze in the second region B is reduced by the application of a voltage. A The change in the transmittance T A The change in the transmittance T A and the transmittance T of the second region B A The difference between decreases with application of voltage.
[0070] The haze of the first region when no voltage is applied is, for example, 1% to 20%, preferably 1% to 10%. The haze of the first region when a voltage is applied is, for example, 1% to 20%, preferably 1% to 10%. The change in haze of the first region due to application of a voltage (|haze when no voltage is applied--haze when voltage is applied|) is, for example, 0% to 20%, preferably 0% to 10%.
[0071] The haze of the second region when no voltage is applied is, for example, 50% to 100%, preferably 70% to 100%. The haze of the second region when a voltage is applied is, for example, 1% to 20%, preferably 1% to 10%. The change in haze of the second region due to application of a voltage (|haze when no voltage is applied--haze when voltage is applied|) is, for example, 30% to 99%, preferably 60% to 99%.
[0072] The amount of change in haze in the first region due to application of a voltage is smaller than the amount of change in haze in the second region due to application of a voltage, and the difference therebetween is, for example, 10% to 99%, and preferably 30% to 99%.
[0073] Transmittance T in the area corresponding to the first area and the area corresponding to the second area of the PDLC film when no voltage is applied A can vary depending on the type and blending ratio of the dichroic dye, and can be appropriately set depending on the purpose.
[0074] Transmittance T of the first region when no voltage is appliedA The transmittance T of the first region when a voltage is applied is, for example, 45% to 95%, and preferably 65% to 95%. A The transmittance T of the first region due to the application of a voltage is, for example, 45% to 95%, and preferably 65% to 95%. A The change in transmittance when no voltage is applied (|T A -Transmittance when voltage is applied T A |) is, for example, 0% to 10%, or, for example, 0% to 5%.
[0075] Transmittance T of the second region when no voltage is applied A The transmittance T of the second region when a voltage is applied is, for example, 40% to 90%, and preferably 40% to 70%. A The transmittance T of the second region by applying a voltage is, for example, 45% to 95%, and preferably 60% to 95%. A The change in transmittance when no voltage is applied (|T A -Transmittance when voltage is applied T A |) is, for example, 5% to 30%, or, for example, 5% to 20%.
[0076] Transmittance T of the first region by applying voltage A and the transmittance T of the second region due to the application of voltage A The difference from the amount of change is, for example, 5% to 25%, or, for example, 5% to 20%.
[0077] The thickness of the PDLC film is, for example, 30 μm to 250 μm, and preferably 50 μm to 150 μm.
[0078] Regarding the PDLC film of the second embodiment, the first transparent conductive film and the second transparent conductive film can be respectively described in the same manner as the first transparent conductive film and the second transparent conductive film in the PDLC film of the first embodiment. Also, regarding the PDLC layer, the same description as the PDLC layer in the PDLC film of the first embodiment can be applied, except that the liquid crystal polymer contained in the liquid crystal droplets in the first region is oriented in a predetermined direction.
[0079] When no voltage is applied, the liquid crystal polymer contained in the liquid crystal droplets in the first region of the PDLC layer is oriented in a predetermined direction. Preferred examples of the orientation direction of the liquid crystal polymer include the thickness direction and a direction perpendicular to the thickness direction. The thickness direction may be at an angle of, for example, 90°±5°, preferably 90°±3°, with respect to the main surface of the transparent conductive film 10, 30.
[0080] A-5. Variation 2 A PDLC film according to another embodiment of the present invention further includes a reflective layer disposed on the side opposite to the viewing side of the PDLC film (specifically, the side opposite to the side on which the PDLC layer of the first transparent conductive film or the second transparent conductive film is disposed). When a PDLC film having such a configuration is observed from the viewing side, in the colorless and transparent state region, light that is incident from the viewing side and reflected by the reflective layer while being suppressed in absorption (coloring) and scattering in the PDLC layer can be observed. Thus, the PDLC film can have a clear appearance in the colorless and transparent state region. On the other hand, in the colored scattering state region, the light that is incident on the PDLC film and reflected by the reflective layer is absorbed (colored) and scattered by the PDLC layer. Thus, the PDLC film can have a colored and opaque matte appearance in the colored scattering state region.
[0081] 3(a) and (b) are schematic cross-sectional views illustrating an example of the PDLC film of this embodiment in a state where no voltage is applied and a state where a voltage is applied, respectively. The PDLC film 100c includes a reflective layer 40, a first transparent conductive film 10, a PDLC layer 20, and a second transparent conductive film 30 in this order. In this case, the second transparent conductive film 30 side of the PDLC film 100c is the viewing side. The reflective layer 40 is laminated on the first transparent conductive film via an adhesive layer (not shown), such as an adhesive layer or a pressure-sensitive adhesive layer. In the PDLC film 100c, the PDLC layer 20 has a first region A in which the liquid crystal droplets 24 include a non-polymerizable liquid crystal component 24a, a liquid crystal polymer 24c, and a dichroic dye 24d, and a second region B in which the liquid crystal droplets 24 include a non-polymerizable liquid crystal component 24a, a polymerizable liquid crystal component 24b, and a dichroic dye 24d.
[0082] As shown in FIG. 3(a), in the PDLC film 100c when no voltage is applied, the first region A and the second region B of the PDLC layer 20 are both in a colored and scattered state. Therefore, when the PDLC film 100c when no voltage is applied is observed from the viewing side, a colored and opaque matte appearance can be observed over the entire surface. On the other hand, as shown in FIG. 3(b), in the PDLC film 100c when a voltage is applied, the first region A of the PDLC layer 20 is in a colored and scattered state, and the second region B is in a colorless and transparent state. Therefore, when the PDLC film 100c when a voltage is applied is observed from the viewing side, a colored and opaque matte appearance can be observed in the first region A, and a clear appearance with high transparency and no or light coloring can be observed in the second region B.
[0083] The configuration of the PDLC layer 20 is not limited to the illustrated example. The PDLC layer 20 may have the same configuration as the PDLC layer 20 included in the PDLC film 100b, or may be made of a liquid crystal component having negative dielectric anisotropy.
[0084] The reflective layer reflects light incident on the viewing side of the PDLC film. The reflective layer may be transmissive, i.e., may be a semi-transmissive reflective layer.
[0085] The total light reflectance of the reflective layer is, for example, 50% or more, preferably 60% or more, and more preferably 70% to 95%.
[0086] When the reflective layer has transparency, its total light reflectance can be, for example, 30% to 60%, preferably 40% to 50%, and its total light transmittance can be, for example, 40% to 70%, preferably 50% to 60%.
[0087] Any appropriate configuration may be adopted as the reflective layer. For example, the reflective layer may be a specular reflective layer or a diffuse reflective layer. By using a specular reflective layer, the change in appearance of the PDLC film between the colorless transparent state and the colored scattering state of the PDLC layer can be increased. The specular reflectance of the reflective layer can be, for example, 25% or more, preferably 40% to 95%. In addition, by using a reflective layer having metallic luster, a metallic luster can be imparted to the appearance of the PDLC film.
[0088] Specific examples of the reflective layer include a resin sheet with high reflectivity (e.g., an acrylic plate); a thin metal plate or metal foil of aluminum, stainless steel, etc.; a vapor-deposited sheet in which aluminum, silver, etc. is vapor-deposited onto a substrate such as a resin film of polyester, etc.; a laminate of a substrate such as a resin film of polyester, etc. and a metal foil such as aluminum, etc.; and a resin film with holes (voids) formed therein.
[0089] The thickness of the reflective layer can be appropriately set depending on the application, etc. The thickness of the reflective layer is, for example, 20 μm to 300 μm, and preferably 30 μm to 100 μm.
[0090] B. Manufacturing method of polymer dispersed liquid crystal film The PDLC film described in section A can be manufactured by any suitable manufacturing method. In one embodiment, the method for manufacturing the PDLC film includes the steps of: (Step A) applying a coating liquid containing a polymer matrix-forming resin, a non-polymerizable liquid crystal component, a polymerizable liquid crystal component, a dichroic dye, and a solvent to a first transparent conductive film to obtain a coating layer; (Step B) drying the coating layer to obtain a PDLC layer including a polymer matrix and liquid crystal droplets including a non-polymerizable liquid crystal component, a polymerizable liquid crystal component, and a dichroic dye dispersed in the polymer matrix; (Step C) laminating a second transparent conductive film over the PDLC layer; and (Step D) irradiating the PDLC layer with active energy rays in a predetermined pattern to form a first region including liquid crystal droplets including a non-polymerizable liquid crystal component, a liquid crystal polymer which is a polymerization product of a polymerizable liquid crystal component, and a dichroic dye; According to the above-mentioned method for producing a PDLC film, it is possible to form a PDLC layer having a first region in which the liquid crystal droplets contain a non-polymerizable liquid crystal component, a liquid crystal polymer, and a dichroic dye, and a second region in which the liquid crystal droplets contain a non-polymerizable liquid crystal component, a polymerizable liquid crystal component, and a dichroic dye, and as a result, it is possible to suitably obtain the PDLC film described in Section A.
[0091] In one embodiment, the active energy ray irradiation in step D is performed in a state where no voltage is applied between the first transparent conductive film and the second transparent conductive film. In another embodiment, the active energy ray irradiation in step D is performed in a state where a voltage is applied between the first transparent conductive film and the second transparent conductive film.
[0092] B-1. Process A In step A, a coating liquid containing a polymer matrix-forming resin, a non-polymerizable liquid crystal component, a polymerizable liquid crystal component, a dichroic dye, and a solvent is applied to a first transparent conductive film to obtain a coating layer.
[0093] The coating liquid is preferably an emulsion in which liquid crystal particles containing a non-polymerizable liquid crystal component, a polymerizable liquid crystal component, and a dichroic dye are dispersed in a solvent (hereinafter, may be referred to as "emulsion coating liquid"). In one embodiment, the coating liquid is an emulsion coating liquid in which polymer matrix forming resin particles and liquid crystal particles containing a non-polymerizable liquid crystal component, a polymerizable liquid crystal component, and a dichroic dye are dispersed in a solvent. The emulsion coating liquid preferably further contains a polymerization initiator, and may further contain any appropriate additive depending on the purpose.
[0094] As the solvent, water or a mixed solvent of water and a water-miscible organic solvent can be preferably used. Examples of the water-miscible organic solvent include C1-3 alcohol, acetone, DMSO, etc. The polymer matrix forming resin, non-polymerizable liquid crystal component, polymerizable liquid crystal component, dichroic dye, and additives and their content ratios are as described in Section A.
[0095] The average particle size of the liquid crystal particles is typically 1 μm or less, for example 0.5 μm or less, preferably less than 0.38 μm, more preferably less than 0.3 μm, even more preferably less than 0.2 μm, even more preferably 0.18 μm or less, even more preferably 0.15 μm or less, even more preferably 0.12 μm or less, and may be, for example, 0.01 μm or more or 0.05 μm or more. The average particle size of the liquid crystal particles is the volume average particle size.
[0096] The particle size of the liquid crystal particles preferably has a relatively narrow particle size distribution. The coefficient of variation (CV value) of the liquid crystal particles may be, for example, less than 0.4, preferably 0.35 or less, and more preferably 0.3 or less.
[0097] The average particle diameter of the resin particles for forming a polymer matrix is preferably 10 nm to 500 nm, more preferably 30 nm to 300 nm, and further preferably 50 nm to 200 nm. Two or more kinds of resin particles having different resin types and / or average particle diameters may be used. The average particle diameter of the resin particles for forming a polymer matrix means the volume average median diameter, and can be measured using a dynamic light scattering particle size distribution measuring device.
[0098] The emulsion coating liquid can be prepared, for example, by mixing a resin emulsion or resin solution containing resin particles for forming a polymer matrix, a liquid crystal emulsion containing liquid crystal particles, and any additives. If necessary, a solvent may be further added during mixing. Alternatively, the emulsion coating liquid can be prepared by adding a non-polymerizable liquid crystal component, a polymerizable liquid crystal component, a dichroic dye, resin particles for forming a polymer matrix, and any additives to a solvent and mechanically dispersing them.
[0099] The resin emulsion and the liquid crystal emulsion can be prepared, for example, by mechanical emulsification, microchannel method, membrane emulsification, etc. Among them, the liquid crystal emulsion is preferably prepared by the membrane emulsification method. According to the membrane emulsification method, an emulsion having a uniform particle size distribution can be suitably obtained. For details of the membrane emulsification method, the disclosures of JP-A-4-355719, JP-A-2015-40994, etc. (these are incorporated herein by reference) can be referred to.
[0100] The solids concentration of the emulsion coating liquid may be, for example, 20% by weight to 60% by weight, and preferably 30% by weight to 50% by weight.
[0101] The viscosity of the emulsion coating liquid can be appropriately adjusted so that the application to the first transparent conductive film is performed suitably. The viscosity of the emulsion coating liquid during application is preferably 20 mPas to 400 mPas, more preferably 30 mPas to 300 mPas, and even more preferably 40 mPas to 200 mPas. If the viscosity is less than 20 mPas, the convection of the solvent becomes significant when the solvent is dried, and the thickness of the PDLC layer may become unstable. If the viscosity exceeds 400 mPas, the bead of the emulsion coating liquid may become unstable. The viscosity of the emulsion coating liquid can be measured, for example, by a rheometer MCR302 manufactured by Anton Paar. The viscosity used here is the shear viscosity value under the conditions of 20°C and a shear rate of 1000 (1 / s).
[0102] The emulsion coating liquid is typically applied to the surface of the first transparent conductive film on the transparent electrode layer side. The first transparent conductive film is as described in Section A.
[0103] Any appropriate method can be adopted as the coating method. For example, roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.), etc. can be mentioned. Among them, roll coating is preferable. For example, the description of JP-A-2019-5698 can be referred to for coating by the roll coating method using a slot die.
[0104] The thickness of the coating layer is preferably 3 μm to 40 μm, more preferably 4 μm to 30 μm, and further preferably 5 μm to 20 μm. Within such a range, a PDLC layer with excellent thickness uniformity can be obtained.
[0105] B-2.Process B In step B, the coating layer is dried to obtain a PDLC layer containing a polymer matrix and liquid crystal droplets containing a non-polymerizable liquid crystal component, a polymerizable liquid crystal component, and a dichroic dye dispersed in the polymer matrix. The solvent is removed from the coating layer by drying, forming a PDLC layer having a structure in which liquid crystal droplets are dispersed in a polymer matrix.
[0106] The coating layer can be dried by any appropriate method. Specific examples of the drying method include natural drying, heat drying, hot air drying, etc. When the emulsion coating liquid contains a crosslinking agent, a crosslinked structure of the polymer matrix can be formed during drying.
[0107] The drying temperature is preferably 20° C. to 150° C., and more preferably 25° C. to 80° C. The drying time is preferably 1 minute to 100 minutes, and more preferably 2 minutes to 10 minutes.
[0108] B-3.Process C In step C, a second transparent conductive film is laminated on the PDLC layer, thereby obtaining a PDLC film having the first transparent conductive film, the PDLC layer, and the second transparent conductive film in this order.
[0109] The second conductive film is as described in section A, and the second transparent conductive film is laminated on the PDLC layer so that the second transparent electrode layer faces the PDLC layer. From the viewpoint of obtaining sufficient adhesion, the lamination is preferably performed using a laminator while applying a lamination pressure of 0.006 MPa / m to 7 MPa / m, more preferably 0.06 MPa / m to 0.7 MPa / m.
[0110] B-4.Process D In step D, the PDLC layer is irradiated with active energy rays in a predetermined pattern to form a first region containing liquid crystal droplets containing a non-polymerizable liquid crystal component, a liquid crystal polymer which is a polymerization product of a polymerizable liquid crystal component, and a dichroic dye. Specifically, in the region irradiated with active energy rays (irradiated region), the polymerizable liquid crystal component in the liquid crystal droplets is polymerized to generate a liquid crystal polymer, and as a result, liquid crystal droplets containing a non-polymerizable liquid crystal compound, a liquid crystal polymer, and a dichroic dye are formed. On the other hand, in the region not irradiated with active energy rays (non-irradiated region), the polymerizable liquid crystal component remains unreacted, and the liquid crystal droplets contain a non-polymerizable liquid crystal component, a polymerizable liquid crystal component, and a dichroic dye. Thus, the irradiated region of the PDLC layer becomes the first region A, and the non-irradiated region becomes the second region B. The liquid crystal polymer contained in the liquid crystal droplets in the first region A is a polymerization product of the polymerizable liquid crystal component contained in the liquid crystal droplets in the second region B. In addition, the content ratio of the non-polymerizable liquid crystal component, the polymerizable liquid crystal component, and the dichroic dye in the droplets in the non-irradiated areas can roughly correspond to the content ratio at the beginning of the formation of the liquid crystal droplets, i.e., the content ratio of the non-polymerizable liquid crystal component, the polymerizable liquid crystal component, and the dichroic dye in the coating liquid.
[0111] The irradiation of the active energy ray is carried out through a photomask with a predetermined pattern. As the active energy ray, ultraviolet rays, infrared rays, X-rays, α rays, β rays, γ rays, electron beams, etc. are used. Among them, ultraviolet rays are preferred. In addition, the active energy ray is preferably a collimated light having high linearity from the irradiation source.
[0112] The ultraviolet irradiation conditions can be appropriately set depending on the type of polymerizable liquid crystal component, the transmittance of the transparent conductive film, the absorption wavelength of the photopolymerization initiator, etc. The irradiation intensity is, for example, 0.1 mW / cm 2 ~1000mW / cm 2 , preferably 1 mW / cm 2 ~100mW / cm 2 The irradiation dose can be, for example, 10 mJ / cm 2 ~10000mJ / cm 2 , preferably 100 mJ / cm 2 ~5000mJ / cm 2 The irradiation temperature may be, for example, from -20°C to 80°C, and preferably from -20°C to 60°C.
[0113] 4 and 5 are schematic diagrams illustrating an example of active energy ray irradiation in the method for producing a PDLC film according to an embodiment of the present invention. In the embodiment shown in FIG. 4, active energy ray irradiation is performed through a photomask 200 in a state where no voltage is applied between the first transparent conductive film 10 and the second transparent conductive film 30. According to this embodiment, in the liquid crystal droplets 24 in the irradiated region of the PDLC layer 20, the polymerizable liquid crystal component 24b is polymerized in a non-oriented state, so that the liquid crystal polymer 24c formed is also in a non-oriented state. Therefore, according to this embodiment, the PDLC film 100a described in Section A can be suitably obtained.
[0114] In the embodiment shown in FIG. 5, the active energy ray irradiation is performed in a state where a voltage is applied between the first transparent conductive film 10 and the second transparent conductive film 30 through a photomask 200. According to this embodiment, in the liquid crystal droplets 24 in the irradiated region of the PDLC layer 20, the polymerizable liquid crystal component 24b is polymerized in a state where it is aligned in a predetermined direction (thickness direction in the illustrated example) along the electric field, and thus a liquid crystal polymer 24c in which the alignment is fixed is formed. Therefore, according to this embodiment, the PDLC film 100b described in Section A can be suitably obtained. The voltage applied during the active energy ray irradiation is not limited as long as the desired alignment (in other words, the haze desired in the first region) is realized, and can be, for example, 10V to 200V, preferably 20V to 100V.
[0115] In one embodiment, by performing active energy ray irradiation using a photomask having a plurality of light-transmitting sections with different aperture ratios, the first region can be formed in the region corresponding to each light-transmitting section at a ratio corresponding to the aperture ratio. Therefore, in the obtained PDLC film, the region corresponding to each light-transmitting section can show a haze corresponding to the aperture ratio when viewed as a whole.
[0116] For example, by using a photomask whose aperture ratio increases continuously from the right end to the left end and irradiating with active energy rays without applying a voltage, a PDLC film can be obtained in which the entire surface is in a colored and scattered state when no voltage is applied, and the haze and color degree increase continuously from the right end to the left end when a voltage is applied.Also, by using a photomask whose aperture ratio increases continuously from the right end to the left end and irradiating with active energy rays while applying a voltage, a PDLC film can be obtained in which the entire surface is in a colorless and transparent state when a voltage is applied, and the haze and color degree decrease continuously from the right end to the left end when no voltage is applied. EXAMPLES
[0117] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring the various properties are as follows. In addition, unless otherwise specified, "parts" and "%" in the examples and comparative examples are based on weight.
[0118] (1) Thickness The measurement was performed using a digital micrometer (manufactured by Anritsu Corporation, product name "KC-351C"). (2) Volume average particle size of liquid crystal particles in liquid crystal emulsion The volume average particle diameter was calculated using a particle size distribution measuring device (manufactured by Microtrac, "MT3300EXII"). (3) Average particle size of resin particles A few drops of the resin dispersion were added to 100 mL of water to prepare a measurement sample. Using a dynamic light scattering particle size distribution analyzer (Microtrac, device name "Nanotrac150"), the measurement sample was placed in the measurement holder of the device, and the device monitor was used to confirm that the concentration was measurable, after which the measurement was performed. (4) Hayes The haze was measured according to JIS K 7136 using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "NDH4000"). (5) Transmittance Measurements were performed using an ultraviolet-visible-near infrared spectrophotometer (Hitachi High-Tech Corporation, product name "UH4150") in accordance with JIS K 7361.
[0119] [Example 1] (First and second transparent conductive films) An ITO layer was formed by sputtering on one surface of a PET substrate (thickness: 50 μm) to obtain a transparent conductive film having a structure of [transparent substrate / transparent electrode layer].
[0120] (Preparation of emulsion coating liquid) A liquid crystal emulsion was prepared by mixing 53.7 parts of a non-polymerizable liquid crystal component (manufactured by JNC, product name "LX-153XX", birefringence Δn = 0.149 (ne = 1.651, no = 1.502), viscosity = 48.5 mPa s), 5.9 parts of a polymerizable liquid crystal component (manufactured by BASF, product name "PALIOCOLOR LC-242"), 0.1 parts of a dichroic dye (manufactured by Hayashibara, product name "G470"), 0.1 parts of a photopolymerization initiator (manufactured by IGM, product name "OMNIRAD651"), 39.8 parts of pure water, and 0.5 parts of a dispersant (manufactured by Daiichi Kogyo Seiyaku, "Noigen ET159") with a homogenizer at 100 rpm for 10 minutes. The average particle size of the liquid crystal particles in the obtained liquid crystal emulsion was 3.4 μm. An emulsion coating liquid (solid concentration: 40 wt%) was obtained by mixing 38.4 parts of the liquid crystal emulsion, 19.1 parts of a polyether-based polyurethane resin aqueous dispersion (manufactured by DSM, product name "NeoRez R967", polymer average particle size: 80 nm, CV value = 0.27, solid content: 40 wt%), 17.0 parts of a polyester-based polyurethane resin aqueous dispersion (manufactured by Sanyo Chemical Industries, product name "Eucoat C-102", polymer average particle size: 168 nm, CV value = 0.23, solid content: 45 wt%), 0.1 parts of a leveling agent (manufactured by DIC, product name "F-444"), and 1.1 parts of a crosslinking agent (tris [3- (2-methylaziridin-1-yl) propionic acid] = propylidine trimethyl), and 24.3 parts of pure water.
[0121] (Application and drying of emulsion coating liquid) The emulsion coating liquid was applied to the ITO layer surface of the first transparent conductive film to form a coating layer having a thickness of 20 μm. The coating was performed using a slot die at a line speed of 6 m / min. The coating layer was then dried at 25° C. for 8 minutes to form a PDLC layer having a thickness of 8 μm.
[0122] (Lamination of the second transparent conductive film) A second transparent conductive film was laminated on the PDLC layer with the ITO layer facing the PDLC layer while applying a lamination pressure of 0.4 MPa / m using a laminator, thereby obtaining a PDLC film.
[0123] (Active energy ray irradiation) On both sides of the PDLC film, a part of the transparent conductive film was half-cut down to the transparent substrate to expose the transparent electrode layer, and the exposed part was used as an extraction electrode. A photomask with a specified pattern was placed on the electrode-treated PDLC film, and the film was exposed to 10 mW / cm under a UV-LED lamp (Hamamatsu Photonics, product name "C11924-101", peak wavelength 365 nm) while applying a voltage of 50 V. 2 The resulting PDLC film was in a colorless and transparent state in the irradiated area and in a colored and scattering state in the non-irradiated area when no voltage was applied.
[0124] [Example 2] A PDLC film was obtained in the same manner as in Example 1, except that ultraviolet light irradiation was performed without applying voltage (applied voltage: 0 V). In the obtained PDLC film, both the irradiated and non-irradiated regions were in a colored and scattering state when no voltage was applied.
[0125] The haze and transmittance were measured in the irradiated and non-irradiated areas of the PDLC film obtained in the examples when an AC voltage of 0V to 50V was applied to the PDLC film using an AC power supply "EC750SA" manufactured by NF Corporation.
[0126] As a result, in the PDLC film of Example 1, the haze and color state in the non-irradiated area were greatly reduced by application of voltage, and both the irradiated area and the non-irradiated area became colorless and transparent. In addition, in the PDLC film of Example 2, the haze and color state in the non-irradiated area were greatly reduced by application of voltage, and the area became colorless and transparent, while the irradiated area remained in a colored and scattered state. From the above, it was confirmed that in all of the PDLC films obtained in the examples, the amount of change in haze and the amount of change in transmittance at the absorption peak wavelength (432 nm) of the dichroic dye due to application of voltage in the first area (irradiated area) were smaller than the amount of change in the second area (non-irradiated area). [Industrial Applicability]
[0127] The PDLC film of the present invention is suitably used for various applications such as displays such as advertisements and guide boards, and smart windows. [Explanation of symbols]
[0128] 100 PDLC Film 10 First transparent conductive film 20 PDLC layers 22 Polymer matrix 24 Liquid Crystal Droplets 24a Non-polymerizable liquid crystal component 24b Polymerizable liquid crystal component 24c Liquid Crystal Polymer 24d dichroic dye 30 Second transparent conductive film
Claims
1. A polymer dispersed liquid crystal film comprising, in this order, a first transparent conductive film, a polymer dispersed liquid crystal layer including a polymer matrix and liquid crystal droplets dispersed in the polymer matrix, and a second transparent conductive film, the polymer dispersed liquid crystal layer has a first region in which the liquid crystal droplets contain a non-polymerizable liquid crystal component, a liquid crystal polymer, and a dichroic dye, and a second region in which the liquid crystal droplets contain a non-polymerizable liquid crystal component, a polymerizable liquid crystal component, and a dichroic dye; Polymer dispersed liquid crystal film.
2. 2. The polymer dispersed liquid crystal film according to claim 1, wherein a change in transmittance at the absorption peak wavelength of the dichroic dye in the first region due to application of a voltage is smaller than a change in the transmittance in the second region.
3. 2. The polymer dispersed liquid crystal film according to claim 1, wherein the liquid crystal droplets have an average particle size of 1 [mu]m or less.
4. 2. The polymer dispersed liquid crystal film according to claim 1, wherein the content of the liquid crystal polymer in the first region is 1 part by weight to 30 parts by weight with respect to 100 parts by weight of the non-polymerizable liquid crystal component.
5. 2. The polymer dispersed liquid crystal film according to claim 1, wherein the content of the dichroic dye in the first region is 0.1 to 10 parts by weight with respect to 100 parts by weight of the non-polymerizable liquid crystal component.
6. 2. The polymer dispersed liquid crystal film according to claim 1, wherein a difference between the haze of the first region and the haze of the second region increases with application of a voltage.
7. 2. The polymer dispersed liquid crystal film of claim 1, wherein a difference between the haze of the first region and the haze of the second region is reduced by application of a voltage.
8. 2. The polymer dispersed liquid crystal film according to claim 1, further comprising a reflective layer on the side of the first transparent conductive film or the second transparent conductive film opposite to the side on which the polymer dispersed liquid crystal layer is disposed.
Citation Information
Patent Citations
Light-modulating film and dimmer
JP2021060521A